(untitled) (Progressive Agriculture, 2019)
Microwaves application could be a potential tool to investigate the influence on different honey quality parameters since it is commonly used in modern kitchen. In this study, microwave sharp R-202 W serial 009157338 was used to analyse the effect of microwave treatment on flower and honeydew honeys by testing the most important honey quality parameters: invertase, diastase, glucoseoxidase and hydroxymethylfurfuraldehyde (HMF). It was examined that the change of these parameters are dependent on further parameters like the moisture content and the pH. However, all the tested enzymes are sensitive to heat. Glucoseoxidase turned out to be the most sensitive followed by invertase and diastase. The analysis showed that the pH of honeys affects the decrease of the enzymatic activities; the lower the pH the stronger the enzyme reduction. HMF, after microwave treatment there was no correlation to the pH. However, there was a slight tendency that honeys with low pH produces more HMF amount than those with higher pH but within both flower and honeydew honeys some samples showed opposite reaction. It was a clear indication that the HMF formation is not only influenced by the pH, there could be other possible factors that might influence the compound and that demand a research work. The effect of the moisture content on the enzyme activities and the HMF amount could be detected after microwave treatment. Progressive Agriculture 30 (1): 125-140, 2019